Leverage Capability as a Strategy to Enhance the Sustainability Performance of Shopping-Mall - Muhammad Iqbal Alamsyah; Agus Rahayu; Vanessa Gaffar; Lili Adi Wibowo (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
The study aims to explore the relationships between Ambidexterity Orientation, Strategic Flexibility, and Leverage Capability in enhancing the Sustainability Performance of shopping-mall. Specifically, it introduces the concept of Leverage Capability Strategy, emphasizing the utilization of external resources to strengthen shopping-mall capabilities and achieve long-term sustainability in a competitive and dynamic market. This research employs a quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM) to analyse data collected from shopping-mall in West Java, Indonesia. This methodology investigates the direct and indirect impacts of Ambidexterity Orientation, Strategic Flexibility, Leverage Capability Strategy on Sustainability Performance. The study shows that Strategic Flexibility significantly improves the Sustainability Performance of shopping-mall, both directly and through Leverage Capability, which utilizes external resources to strengthen capabilities. While Ambidexterity Orientation Influences Sustainability Performance indirectly, it does not have a direct impact on Leverage Capability or Sustainability Performance. These findings highlight the importance of the Leverage Capability Strategy in enhancing Sustainability Performance. The study is limited to shopping-mall in West Java, and its findings may not be fully generalizable to other regions or industries. Further research could expand the geographical scope and incorporate longitudinal analysis to explore temporal dynamics in these relationships. The findings provide actionable insights for mall managers and strategic planners. Strengthening Strategic Flexibility and Leveraging Capability through external resources are critical to achieving Sustainability Performance. This approach can help Shopping-mall adapt to market changes, recover from declining visitor trends, and enhance their competitive edge.